Mengangkat Potensi Local Pelatihan Fotografi Model untuk Masyarakat Umum dan UMKM oleh Mahasiswa USM - M.Alfin Mahbub; Ahmad Hasanauny Rosyid; Laksmana Indra Bunnaya; Erlangga Anang Purwadi; Fernando Briyan Prayoga (Kampus Akademik Publiser, 2024)
The seminar and model photography workshop held at Universitas Semarang aim to develop photography skills for Micro, Small, and Medium Enterprises (MSMEs) in Semarang. This event is designed to provide in-depth understanding and hands-on practice of professional model photography techniques, which are crucial for marketing MSME products. Through various sessions covering basic theory, lighting setup, composition, and the use of modern photography equipment, participants are guided to master the art of producing attractive and high-quality product photos. Additionally, the workshop offers participants the opportunity to learn directly from experienced professional photographers in the industry. By attending this seminar and workshop, it is expected that MSME actors in Semarang will enhance their photography skills, enabling them to present their products more effectively on various digital platforms, ultimately supporting increased sales and business development.